HUBUNGAN ANTARA SIKAP TERHADAP KERJASAMA KELOMPOK DENGAN KEPUASAN KERJA PADA KARYAWAN - KM Amran Nurzaman (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2011)
This research has observed workers in PT Pindad Persero and it purposes to know how correlation dynamic in groups, because the kind of works in this PT Pindad Persero is works that must be done in group. If one of workers cannot cooperate in doing work, the achieved result will not maximum and the relation between partners will not be harmony because there is an assignment load. The research method used is quantitative research with correlative analysis. Taking sample is done by using purposive technique sampling. The measurement tool used is attitude scale and Need Satisfaction Questioner (NSQ) from Porter (1961). The measurement tool is designed by using Likert scale producing the data with ordinal measurement level. The result of data analysis shows rs = -0,125. After doing significance test with test statistic, it is known that t= -0,88, it appropriates with test criteria. In conclusion, there is a correlation in this research but it not so significant, i.e., about 0,156 percent. Basing on processing the data, it concludes that getting higher the attitude of group cooperation is, getting higher the work satisfactory level will be.